With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Roman national ou récit féminin? La littérature des femmes pendant la Révolution tranquille - Boisclair, Isabelle (Globe, 1999)
Bien que l’on situe habituellement l’émergence du mouvement de l’écriture des femmes au milieu des années 1970, la production littéraire des femmes connaît une hausse importante en 1961 et la majorité de ces oeuvres, à l’instar de celles des hommes, participent d’un mouvement d’émancipation. Une relecture au féminin permet de déceler la portée contestataire contenue dans les oeuvres des femmes dès le début des années soixante. Durant la Révolution tranquille, pendant que les écrivains élaborent le « roman national », les femmes écrivent le « récit féminin ». Si l’écriture masculine tente d’affirmer sa québécitude et de s’émanciper du colonialisme, l’écriture des femmes tente d’affirmer sa spécificité sexuelle et de s’émanciper du patriarcat. Toutefois, les instances de réception critique ne perçoivent pas cette voix divergente, tout occupées qu’elles sont à détecter les signes de l’affirmation nationale.
Keywords: 1900-1999; 1960-1969; amériques; approches et analyses; arts; canada; cours; discipline; lit3495; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

La mère des herbes de Jovette Marchessault : quand le littéraire est politique - Côté, Audrey (Université du Québec à Montréal, 1999)
Keywords: IREF; amériques; approches et analyses; arts; discipline; europe; france; mémoires/thèses; patriarcat; québec; régions géographiques; systèmes d'oppressions; études littéraires

Quand écrire, c'est agir: stratégies narratives d'agentivité féministe dans Journal pour mémoire de France Théoret - Havercraft, Barbara (Dalhousie French Studies, 1999)
Keywords: amériques; approches et analyses; arts; canada; cours; discipline; lit3495; patriarcat; premier cycle; québec; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Routledge, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques

Gender, ‘Race’, Ethnicity in Art Practice in Post-Apartheid South Africa: Annie E. Coombes and Penny Siopis in Conversation * - Coombes, Annie E. (Feminist Review, 1997)
Siopis has always engaged in a critical and controversial way with the concepts of ‘race’ and ‘ethnicity’ in South Africa. For politically sensitive artists whose work has involved confronting the injustices of apartheid, the current post-apartheid situation has forced a reassessment of their practice and the terms on which they might engage with the fundamental changes which are now affecting all of South African society. Where mythologies of race and ethnicity have been strategically foregrounded in the art of any engaged artist, to the exclusion of many other concerns, the demise of apartheid offers the possibility of exploring other dimensions of lived experience in South Africa. For feminists, this is potentially a very positive moment when questions of gender – so long subordinated to the structural issue of ‘race’ under apartheid – can now be explored. Penny Siopis’ work has long been concerned with the lived and historical relations between black and white women in South Africa. The discussion focuses on the ambivalent and dependent relationships formed between white middle-class women and black domestic labour during apartheid. Siopis’ work engages with how the appropriation of black women's time, lives, labour and bodies has shaped her ‘own’ history.
Disponible en ligne: https://link-springer-com.proxy.bibliotheques.uqam.ca/article/10.1057/fr.1997.7
Keywords: afrique; afrique du sud; antiracisme; apartheid; approches et analyses; arts; cours; discipline; droit des femmes*; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Minnesota University Press, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Contenu: Introduction / Aamir Mufti and Ella Shohat – pt. I. Contesting Nations. 1. Zionism from the Standpoint of Its Victims / Edward W. Said. 2. Sephardim in Israel: Zionism from the Standpoint of Its Jewish Victims / Ella Shohat. 3. Of Balkans and Bantustans: Ethnic Cleansing and the Crisis in National Legitimation / Rob Nixon. 4. "No Longer in a Future Heaven": Gender, Race, and Nationalism / Anne McClintock. 5. Currying Favor: The Politics of British Educational and Cultural Policy in India, 1813-54 / Gauri Viswanathan. 6. The Nation as Imagined Community / Jean Franco – pt. II. Multiculturalism and Diasporic Identities. 7. On the Question of a Theory of (Third) World Literature / Madhava Prasad. 8. Caliban Speaks Five Hundred Years Later / Roberto Fernandez Retamar. 9. The Local and the Global: Globalization and Ethnicity / Stuart Hall. 10. Multiculturalism and the Neoconservatives / Robert Stam. 11. Shuckin' Off the African-American Native Other: What's "Po-Mo" Got to Do with It? / Wahneema Lubiano. 12. Identity, Meaning, and the African-American / Michael Hanchard. 13. Just Looking for Trouble: Robert Mapplethorpe and Fantasies of Race / Kobena Mercer – pt. III. Gender and the Politics of Race. 14. Under Western Eyes: Feminist Scholarship and Colonial Discourses / Chandra Talpade Mohanty. 15. Traddutora, Traditora: A Paradigmatic Figure of Chicana Feminism / Norma Alarcon. 16. American Indian Women: At the Center of Indigenous Resistance in Contemporary North America / M. Annette Jaimes and Theresa Halsey. 17. "On the Threshold of Woman's Era": Lynching, Empire, and Sexuality in Black Feminist Theory / Hazel V. Carby. 18. Making Empire Respectable: The Politics of Race and Sexual Morality in Twentieth-Century Colonial Cultures / Ann Laura Stoler. 19. Age, Race, Class, and Sex: Women Redefining Difference / Audre Lorde. 20. Gender Is Burning: Questions of Appropriation and Subversion / Judith Butler. 21. Sisterhood: Political Solidarity between Women / Bell Hooks – pt. IV. Postcolonial Theory. 22. Not You/Like You: Postcolonial Women and the Interlocking Questions of Identity and Difference / Trinh T. Minh-ha. 23. Is the "Post-" in "Postcolonial" the "Post-" in "Postmodern"? / Kwame Anthony Appiah. 24. The World and the Home / Homi K. Bhabha. 25. Reading Africa through Foucault: V.Y. Mudimbe's Reaffirmation of the Subject / Manthia Diawara. 26. Teaching for the Times / Gayatri Chakravorty Spivak. 27. Postcolonial Criticism and Indian Historiography / Gyan Prakash. 28. The Postcolonial Aura: Third World Criticism in the Age of Global Capitalism / Arif Dirlik. Le texte "Age, Race, Class, and Sex : Women Redefining Difference" de Audre Lorde a été donné en lecture au cours LIT4700.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Les lesbiennes et le roman français 1796-1996 - Waelti-Walters, Jennifer (Nouvelles Questions Féministes, 1997)
La lesbienne telle qu'on la connaît aujourd'hui est entrée dans le roman français avec La Religieuse de Diderot (pub. 1796), et jusqu'en 1926 elle est créée et recréée presqu'exclusivement par les écrivains hommes qui modèlent leurs personnages sur Margarita de La Fille aux yeux d'or de Balzac et Mademoiselle de Maupin de Gautier, pour en faire des femmes menaçantes pour la virilité collective. A partir de 1930 les expériences littéraires lesbiennes sont prises en charge par des auteures femmes qui en explorent les secrets, les misères et les oppressions d'abord, et ensuite — à partir de l'oeuvre de Monique Wittig et de Jocelyne François — la vie quotidienne dans sa variété. Cet article est un compte rendu d'unprojet de recherche en cours — projet qui étudie un territoire littéraire jusqu'ici totalement ignoré dans l'histoire du roman.
Keywords: approches et analyses; arts; discipline; discours dominant; europe; france; histoire du roman; hétérosexisme; patriarcat; personnes lesbiennes; régions géographiques; systèmes d'oppressions; études littéraires

Moi, Tituba sorcière –: noire de Salem - Condé, Maryse; De Serres, Murielle; Thérien, Michel; Jean, Julie (Beauchemin, 1995)
Fille d'une esclave violée par un marin anglais à bord d'un vaisseau négrier, Tituba, née à la Barbade, est initiée aux pouvoirs surnaturels par Man Yaya, guérisseuse et faiseuse de sorts. Son mariage avec John Indien l'entraîne à Boston puis au village de Salem, au service du révérend Samuel Parris. Elle est emprisonnée à la suite du procès des sorcières de Salem en 1692.
Section: 223 p., [16] p. de planches : ill. en coul.
Keywords: afro-féminisme; amériques; approches et analyses; arts; barbade; caraïbes; cours; discipline; féminismes noirs; histoire et politique; lit2815; premier cycle; roman; régions géographiques; système colonial; systèmes d'oppressions; thématiques; états-unis; études littéraires

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Identités en devenir et famille subvertie dans l'oeuvre de Jovette Marchessault - Poirier, Martin (Université du Québec à Montréal, 1995)
Ce mémoire présente une analyse du roman Des cailloux blancs pour les forêts obscures (Montréal: Leméac, 1987) de Jovette Marchessault. L'approche théorique utilisée est avant tout inspirée du travail de Marianne Hirsch (The Mother/Daughter Plot, 1989) qui revoit la notion de «roman familial» de Freud d'un point de vue féministe. Les réflexions de Luce Irigaray et de Claire Lejeune à propos de la notion identitaire et de la constitution de famille servent également à l'analyse. La question principale qui guide l'ensemble des quatre chapitres du mémoire est la suivante: en quoi les remises en question identitaires des personnages féminins et masculins arrivent-elles à transformer les structures de la famille patriarcale et les caractéristiques du roman familial traditionnel?
Keywords: amériques; approches et analyses; arts; discipline; famille; mémoires/thèses; patriarcat; québec; régions géographiques; systèmes d'oppressions; thématiques; études littéraires

The lesbian postmodern - Doan, Laura L. (Columbia University Press, 1994)
Tous originaux de ce volume, ces essais évocateurs rédigés par des chercheureuses tels que Robyn Wiegman, Elizabeth Grosz et Judith Roof examinent un domaine encore intact de la critique littéraire et culturelle et de la théorie du genre, une postmodernité spécifiquement lesbienne. Les essais retracent, d’une part, comment certaines théories et productions culturelles lesbiennes mettent en avant une politique de différence et de marginalité et critiquent ainsi l’hégémonie patriarcale et hétérosexuelle. D’un autre côté, certains essais soulignent comment une esthétique postmoderne, avec sa valorisation de la différence, de la pluralité sexuelle et du flou des genres, contribue à la production culturelle lesbienne. Parmi les sujets abordés figurent les définitions changeantes des termes lesbien et postmoderne ; le potentiel et danger de ce nouveau territoire conceptuel dans la théorie, la représentation littéraire et visuelle et la culture populaire ; la lesbienne dans le cinéma hollywoodien ; les actrices Jodie Foster et Sandra Bernhard ; et des œuvres de Jeanette Winterson, Michelle Cliff et Gloria Anzaldua. Tout au long, les contributeurices abordent les questions et enjeux interdépendants de classe, de race, d’ethnicité, de postcolonialisme et de marchandisation.
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; patriarcat; personnes lesbiennes; postmodernisme; sexisme; système colonial; systèmes d'oppressions; études littéraires

Ecrire comme vivre: dans l'hybridite: entretien avec Anne-Marie Alonzo - Dupre, Louise (Voix et Images, 1994)
Keywords: EDI; amériques; approches et analyses; arts; canada; capacitisme; cours; discipline; lit2815; lit3495; premier cycle; québec; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Questionnement féministe de l'univers symbolique patriarcal au théâtre à partir d'un cadre d'analyse psychologque jungien ; suivi d'une expérimentation pratique intitulée Ailleurs - Hamel, Monique (Université du Québec à Montréal, 1994)
Keywords: IREF; amériques; approches et analyses; arts; discipline; mémoires/thèses; patriarcat; québec; régions géographiques; systèmes d'oppressions; théâtre

Femmes, art et pouvoir et autres essais - Nochlin, Linda (Jacqueline Chambon, 1993)
Plusieurs essais, rédigés à partir de 1969, qui abordent les sujets des représentations féminines dans l'art, entre la fin du XVIIIe siècle et le XXe siècle, l'érotisme et les images du féminin dans l'art du XIXe siècle et la question pourquoi n'y a-t-il pas eu de grands artistes femmes. L'auteur identifie l'idéologie dominante sur laquelle repose la place donnée aux femmes.
Première publication: 1991 Titre original: Women, Art, and Power, and Other Essays.
Keywords: approches et analyses; arts; cours; discipline; discours dominant; domination masculine; fem1000; har4600; har4610; histoire de l'art; histoire et politique; premier cycle; rapports de domination; rapports sociaux de sexe; systèmes d'oppressions; thématiques; théories féministes

Pourquoi n'y-a-t-il pas eu de grands artistes femmes? - Nochlin, Linda (Femmes, art et pouvoir., 1993)
Première publication : 1991
Keywords: approches et analyses; arts; cours; discipline; domination masculine; fem1000; histoire de l'art; histoire et politique; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; théories féministes

When Jack Blinks: Si(gh)ting gay desire in Ann Bannon's Beebo Brinker - Barale, Michèle Aina (Feminist studies, college park, 1992)
The overtly lesbian story, "Beebo Brinker," by Ann Bannon offers the heterosexual male reader an opportunity to engage in nonheterosexual imaginings. Bannon's story is examined for its subcultural appropriation and subversion as a crossover novel in reverse.
https://www-proquest-com.proxy.bibliotheques.uqam.ca/docview/233183798/fulltextPDF/6501A30CCBE14AACPQ/1?accountid=14719
Keywords: approches et analyses; arts; discipline; hétérosexisme; identités LGBTQIA2+; lesbianisme; ressource en ligne; systèmes d'oppressions; études littéraires

L'écrivain - Brossard, Nicole (La nef des sorcières, 1992)
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*; études littéraires

La nef des sorcières - Guilbeault, Luce; Blackburn, Marthe; Théoret, France; Gagnon, Odette; Blais, Marie-Claire; Pelletier, Pol; Brossard, Nicole; Guilbeault, Luce (L'Hexagone, 1992)
La création au Théâtre du Nouveau Monde de La nef des sorcières, pièce composée de sept textes d’auteures différentes, est reconnue comme un moment capital dans l’émergence du théâtre féministe militant au cours des années 1970 et 1980. En ce qui concerne la réception de ce spectacle et du texte publié, l’attention du public et de la critique se dirigeait surtout vers la thématique féministe véhiculée par la pièce et le commentaire qui s’y faisait sur le fonctionnement du patriarcat dans la vie privée des femmes. Cependant, l’objectif des auteures et des comédiennes dépassait largement le simple commentaire social. Ce n’était pas leur intention de réduire la scène théâtrale à une simple tribune politique. Luce Guilbeault, qui initia le projet et s’y engagea comme metteure en scène, auteure et comédienne, voulait avec les autres, en plus de susciter des discussions, ébranler les fondements sexistes du théâtre, élargir l’espace de l’imaginaire collectif, transformer la symbolique masculiniste de la culture québécoise, et élargir l’horizon d’attente de l’auditoire. Quand son Actrice en folie subit un trou de mémoire et enlève son costume dès son entrée en scène, c’est une ouverture remarquable au spectacle expérimental et à l’invention d’une nouvelle théâtralité au féminin qui se fait jour. C’est alors que commence la remise en cause radicale des pratiques, des codes, des règles et des conventions du jeu, des langages et de la forme canoniques du théâtre qui permettent depuis des millénaires l’esthétisation par le théâtre des idéologies et des fantasmes dominants sexistes.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; discipline; fem1000; pratiques féministes; premier cycle; périodes historiques; québec; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théâtre; écriture des femmes*

Sororophobia: Differences among women in literature and culture. - Michie, Helena (Oxford University Press, 1992)
This book looks at how differences among women have been textually represented at a variety of historical moments and in a variety of cultural contexts, including Victorian mainstream fiction, African-American mulatto novels, late twentieth-century lesbian communities, and contemporary country music. Sororophobia designates the complex and shifting relations between women's attempts to identify with other women and their often simultaneous desire to establish and retain difference. Michie argues for the centrality to feminism of a paradigm that moves beyond celebrations of identity and sisterhood to a more nuanced notion of women's relations with other women which may include such uncomfortable concepts as envy, jealousy, and competition as well as more institutionalized ideas of difference such as race and class. Chapters on literature are interspersed by "inter-chapters" on the choreography of sameness and difference among women in popular culture.
Keywords: approches et analyses; arts; classisme; discipline; histoire et politique; littérature; racisme; relations entre femmes*; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

New lesbian criticism: Literary and cultural readings - Munt, Sally (Columbia University Press, 1992)
This volume explores whether there can be a specific lesbian aesthetic, juxtaposed against reading as a woman´ or as a heterosexual´. Contributors both explore the uses of recent theories such as post-structuralism and offer a lesbian critique of such methodologies. Close readings of contemporary lesbian fiction and popular culture focus on works such as Zami, Oranges Are Not the Only Fruit, The Wanderground, and Desert of the Heart as well as on lesbian pornography. Together the essays point to lesbian culture´s ability to create new meanings for iteself and to foreground the intertextuality of lesbian identities. Contributors: Sonya Andemahr, Lisa Henderson, Hilary Hinds, Katie King, Reina Lewis, Sally Munt, Gillian Spraggs, Angela Weir, Anna Wilson, Elizabeth Wilson, and Bonnie Zimmerman.
Keywords: 1900-1999; approches et analyses; arts; discipline; hétérosexisme; personnes lesbiennes; périodes historiques; systèmes d'oppressions; études culturelles; études littéraires

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

Frontiers: Selected essays and writings on racism and culture, 1984-1992 - Philip, Marlene Nourbese (Mercury Press, 1992)
Cette collection d'essais tant attendue se compose d'écrits sélectionnés parmi les nombreuses apparitions de la boursière Guggenheim Marlene Nourbese Philip dans des magazines, des journaux et des revues, y compris FUSE . Mordant, élégant, tour à tour farouchement interrogateur, magiquement lyrique et doucement explorateur, l'examen par Philip des questions contemporaines de race et de culture est toujours éloquent et impérieux.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; arts; cours; discipline; fem1000; inégalités; littérature; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Une Chambre à soi - Woolf, Virginia; Malraux, Clara (Denoël, 1992)
Bravant les conventions avec une irritation voilée d'ironie, Virginia Woolf rappelle dans ce délicieux pamphlet comment, jusqu'à une époque toute récente, les femmes étaient savamment placées sous la dépendance spirituelle et économique des hommes et, nécessairement, réduites au silence. Il manquait à celles qui étaient douées pour affirmer leur génie de quoi vivre, du temps et une chambre à soi. " Pourquoi un sexe est-il si prospère et l'autre si pauvre ? Quel est l'effet de la pauvreté sur le roman ? " Virginia Woolf
Section: 171 pages ; 21 cm
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; europe; lit2815; lit3220; lit3495; premier cycle; périodes historiques; royaume-uni; régions géographiques; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

L'interloquée ; Les oubliées de l'oubli ; [et] Dé/générée - Causse, Michèle (Trois, 1991)
« L’androlecte est en effet un soliloque. C’est la production mentale, disons la pathologie langagière, de l’Andros qui, victime d’une faille principielle, n’a pas su, pas pu, pas voulu accéder au chiffre deux et qui, s’étant érigé en seul locuteur, n’a pas eu d’autre interlocuteur que lui-même. Avant même de parler, une femme en "Androlecte est inter-loquée". Soit au sens propre "interdite-interrompue". Le dictionnaire – depôt sacré des mots de l’androlecte – ne donne-t-il pas comme exemple cette phrase, ô combien illuminante: "Faute d’interlocuteur, elle se parlait à elle-même". (Petit Robert, Léon Bloy). Bécassine ayant cru sans doute dans le langage comme communication. » p.15 éditions Trois, 1990
Keywords: approches et analyses; arts; discipline; hétérosexisme; lesbianisme; sexisme; systèmes d'oppressions; études littéraires

Surrealism and women - Caws, Mary Ann; Kuenzli, Rudolf E.; Raaberg, Gloria Gwen (MIT Press, 1991)
These sixteen illustrated essays present an important revision of surrealism by focusing on the works of women surrealists and their strategies to assert positions as creative subjects within a movement that regarded woman primarily as an object of masculine desire or fear.While the male surrealists attacked aspects of the bourgeois order, they reinforced the traditional patriarchal image of woman. Their emphasis on dreams, automatic writing, and the unconscious reveal some of the least inhibited masculine fantasies. The first resistance to the male surrealists' projection of the female figure arose in the writings and paintings of marginalized woman artists and writers associated with Surrealism. The essays in this collection explore the complexity of these women's works, which simultaneously employ and subvert the dominant discourse of male surrealists.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

A lure of knowledge: Lesbian sexuality and theory - Roof, Judith (Columbia University Press, 1991)
Lesbianism in literature has been dealt with rather indirectly in the past. Editors have led readers to the "artistry" of a work containing lesbianism, emphasizing instead the literary history and historical context of the work rather than the representations of lesbianism. The editor for Colette's The Pure and the Impure, for instance, affirms that Colette has a knowledge of a "strange sisterhood," but assures readers she has never strayed from the "normal." In the groundbreaking A Lure of Knowledge, Judith Roof demonstrates that representations of lesbian sexuality occupy specific locations or positions in the arguments, subject matter, and rhetoric of Western European and American literary criticism. She examines the political context of representations: how lesbian sexuality is used as a signifier an why it appears when and where it does. Roof argues that attempts to depict or explain lesbian sexuality spur anxieties about knowledge and identity. In reaction to and denial of these anxieties, lesbian sexuality is represented in film, literature, theory, and criticism as foreplay, as simulated heterosexuality, as erotic excess, as joking inauthenticity, as artful compromise, or as masculine mask in a specific repertoire of neutralization and evasion. Challenging the heterosexism of film theory and feminist theory, this book analyzes the rhetorical use of lesbian sexuality. Roof explores a range of discourses, from the woks of such authors as Anais Nin, Olga Broumas, Julia Kristeva, Jane Rule, Luce Iriguray, and Sigmund Freud, to films such as Emmanuelle, Desert Hearts, Entre Nous, and I've Heard the Mermaids Singing, to professional tennis.
Keywords: approches et analyses; arts; cinéma; communication; discipline; hétérosexisme; lesbianisme; personnes lesbiennes; sexualité; sexualité lesbienne; systèmes d'oppressions; thématiques; études culturelles; études littéraires

De la mère patriarcale à la mère légendaire : Triptyque lesbien de Jovette Marchessault - Saint-Martin, Lori (Voix et Images, 1991)
Keywords: amériques; approches et analyses; arts; discipline; histoire et politique; maternité; patriarcat; personnes lesbiennes; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; études littéraires